Vascular mineralization associated with bone mineral disorder in a patient with chronic kidney disease - case report (Research, Society and Development, 2020)
Chronic kidney disease (CKD) is a common condition in the small animal practice and its presence is associated with polysystemic changes, such as bone mineral disorders related to the action of uremic toxins such as parathyroid hormone (PTH). The imbalance of homeostasis caused by excess PTH can lead to clinical repercussions such as fibrous osteodystrophy, tissue calcifications and progression of kidney disease. The aim of the present report is to describe the case of a four-year-old dog with CKD associated with bone mineral disorder with systemic repercussions such as fibrous osteodystrophy, arterial hypertension, concentric left ventricular hypertrophy and vascular calcifications.